Soilless Culture-An Intensive Production Method on Its Way to Sustainability - Gruda, Nazim; Machado, Rui Manuel Almeida; van Os, Erik (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Soilless Culture Systems (SCSs) have expanded globally into protected and open-field horticulture. However, it is crucial to ensure the sustainability of this system in order to address resource challenges, minimize environmental impacts and establish a resilient and efficient agricultural system in the face of global challenges. This Special Issue reprint emphasizes the significance of transitioning to sustainable horticultural practices, outlines the challenges encountered, and presents various strategies to reduce or eliminate the utilization of peat in growing media. Additionally, it introduces cascade systems strategies that include recycling nutrient solutions, minimizing pesticide emissions, and integrating eco-friendly practices. Utilizing microorganisms has been identified as a potential strategy to augment the resilience of plants against the onslaught of pests and diseases. This approach is expected to reduce the utilization of chemicals for the same purpose considerably. This Special Issue reprint significantly contributes to advancing sustainable SCSs and growing media, providing diverse strategies and insights in order to propel its progress as a viable form of sustainable agriculture. It comprises 11 original contributions and an editorial written by 45 authors from 10 different countries. These numbers differ slightly from what was reported in the Editorial, as the Editorial was written before the last article was published.